MANAGEMENT OF HAZARDOUS AND TOXIC WASTE (B3) AT MENTAL HOSPITAL X IN MEDAN CITY - Siti Romaito Siregar; Fatma Indriani; Ruhul Masyithah; Rini Warahmah Batubara; Adelia Putri; Dwi Adelia Putri Harahap (HEARTY, 2026)
Management of hazardous and toxic medical waste (B3) in hospitals is an important aspect in efforts to maintain environmental safety and public health. This study aims to determine the flow of B3 medical waste management at Mental Hospital X, Medan City, which includes the stages of waste sorting, storage, and transportation. This type of research is descriptive observational with a cross-sectional approach, using secondary data from the Environmental Sanitation Installation for the period January–September 2025. The results of the study indicate that the overall management of B3 medical waste is not optimal and does not meet standards. The sorting stage has not been carried out based on the type of waste, where all waste (sharp, soft, pharmaceutical) is mixed without labeling. The storage stage at the Temporary Storage Place (TPS) for B3 medical waste also does not meet design requirements, such as the building is not closed, not watertight, not equipped with hazard symbols, and emergency facilities. Although transportation has collaborated with a licensed third party (PT X), the risk remains due to the transported waste being mixed and not properly sorted. In conclusion, Mental Hospital X has critical non-conformities in the management of B3 medical waste. Therefore, fundamental improvements, especially in sorting at source and renovation of TPS, are urgent to reduce the risk of contamination and environmental impacts.